Divided by Faith (in Christian America): Christian Nationalism, Race, and Divergent Perceptions of Racial Injustice. (11th November 2021) - Perry, Samuel L; Cobb, Ryon J; Whitehead, Andrew L; Grubbs, Joshua B
Abstract: Sociologists have long identified a "perception gap" between Black and White Americans regarding racial injustice, often emphasizing either "epistemologies of ignorance" or "religio-cultural" mechanisms. Integrating and extending these insights, we theorize that conceptions of America's religio-cultural heritage and identity are racially coded and grounded in White supremacy, but only for those atop the racial hierarchy. From this, we predict the perception gap is largely driven by Whites' racialized idealization of their own religio-cultural preeminence in American civic life—what we call "White Christian nationalism." Drawing on nationally representative data with currently relevant measures of Americans' perceptions of racial injustice, we show the more Whites affirm seemingly race-neutral statements promoting Christianity's preeminence in American life, the more they affirm White victimhood and deny anti-Black injustice. This association seems to drive the perception gap. Specifically, for Whites, Christian nationalism is powerfully associated with refusing to acknowledge anti-Black discrimination while affirming supposed anti-White discrimination; lower likelihood of attributing Ahmaud Arbery's murder to racism or to even know about the incident; and greater likelihood of denying racial inequality in policing. For Black Americans, however, affirming the same measures of Christian nationalism produces no consistent change in their recognition of racial injustice. Thus, for Whites, appeals to America's "Christian" heritage are racially coded and contribute to an ideological defense of White supremacy, including the denial of blatant anti-Black injustice and a commitment to White victimhood.